Association of Chronic Stress with Cardiovascular Diseases: A Single Centre Experience (Medicine Today, 2024)
Introduction: Cardiovascular diseases (CVD) pose a growing global health threat, with a 42.4% increase in deaths between 1990 and 2015 despite a 27.3% decline in age-standardized CVD mortality rates. Risk factors like smoking, inactivity, high blood pressure, obesity, hyperinsulinemia, hypercholesterolemia, and psychological stress contribute to CVD. Aim of the study: The study aims to assess the prevalence of stress and its association with cardiovascular diseases (CVD). Materials and Methods: This prospective study at Jessore Medical College and Hospital, Bangladesh, involved 110 patients aged 25-64 with cardiovascular diseases (CVDs) and chronic stress. The study duration was one year from January 2022 to December 2022. Result: The majority (54.55%) were aged 31-40, with females constituting 57.00% of the total sample. Work experience distribution revealed 50.91% with 1-10 years, 21.82% with 11-20 years, and 27.27% with over 20 years. Stress intensity analysis showed no mild stress, 71.82% with "Average to acute stress," 25.45% with "Average stress," and 2.73% with acute stress. Cardiovascular risk factors included 19.00% lacking sleep, 15.00% with low physical activity, and 12.00% each for smoking, hypercholesterolemia, and arterial hypertension. Conclusion: Research indicates that individuals experiencing stress face significant cardiovascular risk factors. However, the connections between stress and these risk factors appear complex and must be more apparent. This underscores the necessity for additional investigation into the relationship between stress and other cardiovascular risk factors while considering factors such as age, gender, and socio-economic characteristics within the population.Medicine Today 2024, Vol.36 (2): 127-131